2008
DOI: 10.1002/adfm.200800099
|View full text |Cite
|
Sign up to set email alerts
|

Band‐Edge Engineered Hybrid Structures for Dye‐Sensitized Solar Cells Based on SnO2 Nanowires

Abstract: In this report, we show for the first time that SnO2 nanowire based dye sensitized solar cells exhibit an open circuit voltage of 560 mV, which is 200 mV higher than that using SnO2 nanoparticle based cells. This is attributed to the more negative flat band potential of nanowires compared to the nanoparticles as determined by open circuit photo voltage measurements made at high light intensities. The nanowires were employed in hybrid structures consisting of highly interconnected SnO2 nanowire matrix coated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
268
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 422 publications
(273 citation statements)
references
References 44 publications
3
268
1
1
Order By: Relevance
“…Initial demonstrations of DSSCs were based on dye sensitization of porous nano crystalline semiconductors like TiO 2 . There are numerous studies on the potentials of improving the efficiency of DSSCs by using other semiconducting metal oxides, such as Nb 2 O 5 [3], CeO 2 [4], ZnO [5,6], and SnO 2 [7] and composite oxide materials [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Initial demonstrations of DSSCs were based on dye sensitization of porous nano crystalline semiconductors like TiO 2 . There are numerous studies on the potentials of improving the efficiency of DSSCs by using other semiconducting metal oxides, such as Nb 2 O 5 [3], CeO 2 [4], ZnO [5,6], and SnO 2 [7] and composite oxide materials [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…High light absorption is enabled by nanostructures, which provides a large surface area to increase the conversion efficiency of the cells. [6][7][8][9][10][11] The authors recently reported a successful growth of SnO 2 by atomic layer deposition (ALD) at 60-250 o C by using a newly 30 synthesized cyclic amide of Sn(II) (1,3-bis(1,1-dimethylethyl)-4,5-dimethyl-(4R,5R)-1,3,2-diazastannolidin-2-ylidene) and 50 wt.% hydrogen peroxide (H 2 O 2 ). 12 The growth per cycle was as high as 1.8 Å/cycle and the lowest resistivity of ~2×10 -2 ohm·cm was obtained at a growth temperature of 120 o C. In order to get 35 conformal growth of SnO 2 on structures with high aspect-ratios, the growth temperature needed to be lowered to ~60 o C to extend the lifetime of H 2 O 2 molecules diffusing inside narrow features.…”
Section: Introductionmentioning
confidence: 99%
“…Remedial core-shell NWs (with a ZnO core and TiO 2 shell) [44] have been used in order to benefi t from the charge transport of the crystalline ZnO NW and surface stability and charge transfer characteristics of the TiO 2 shell, but the approach has so far met with limited success (PCE ≈ 2.1%) [45]. Tin oxide NWs with an atomic layer TiO 2 NPs have been used with greater success, achieving PCE of ~4.1% (V oc = 0.72 V) compared with 2.1% for the pure SnO 2 -NW DSSC [46]. Solar cells employing QD-sensitized ZnO NW solar cells with a similar I 2 /I 3 -redox couple (as in a DSSC) with PCE of 0.4% (V oc = 0.6 V) have been reported [47].…”
Section: Photovoltaicsmentioning
confidence: 99%